2021
DOI: 10.3390/cancers13040669
|View full text |Cite
|
Sign up to set email alerts
|

Drug Combination in Cancer Treatment—From Cocktails to Conjugated Combinations

Abstract: It is well recognized today that anticancer drugs often are most effective when used in combination. However, the establishment of chemotherapy as key modality in clinical oncology began with sporadic discoveries of chemicals that showed antiproliferative properties and which as a first attempt were used as single agents. In this review we describe the development of chemotherapy from its origins as a single drug treatment with cytotoxic agents to polydrug therapy that includes targeted drugs. We discuss the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 205 publications
(224 reference statements)
0
53
0
Order By: Relevance
“…It is now widely recognized that therapeutic approaches that combine two or more agents can result in a synergistic effect through different mechanisms of action [145]. For example, HDAC9 inhibitors administered in combination with conventional anti-tumor agents or novel target-specific agents (that target known cancer-associated pathways for each type of cancer) may increase therapeutic efficacies.…”
Section: Conclusion and Clinical Perspectivesmentioning
confidence: 99%
“…It is now widely recognized that therapeutic approaches that combine two or more agents can result in a synergistic effect through different mechanisms of action [145]. For example, HDAC9 inhibitors administered in combination with conventional anti-tumor agents or novel target-specific agents (that target known cancer-associated pathways for each type of cancer) may increase therapeutic efficacies.…”
Section: Conclusion and Clinical Perspectivesmentioning
confidence: 99%
“…Several compounds from natural products have been reported to improve the therapeutic outcomes of cancer patients when used in combination with chemotherapeutic drugs. Combining these treatments can induce synergetic effects, inhibit side effects, or overcome drug resistance [ 7 , 8 , 11 ]. Previous studies have suggested the synergistic action of PGG with the traditional chemotherapeutic drug 5-FU in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It can target critical pathways in a synergistic or additive manner. This approach potentially reduces drug resistance and the chemotherapeutic drug doses in the regimen, helping to circumvent the severe side effects while providing anti-cancer benefits [ 7 , 8 ]. Increasing evidence has suggested that plant polyphenols might be combined with conventional therapy (chemo/radiotherapy) to sensitize tumor cells to the treatment by inhibiting the pathway that leads to treatment resistance [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing the ability to directly test a range of drugs in a patient, the use of IMDs in gliomas offer significant opportunities to answer questions which so far have been elusive: Firstly, this strategy allows to safely test the efficacy of drug combinations, which are commonly used in other cancers 37 , but only rarely in glioblastomas, despite significant preclinical evidence that different drugs acting synergistically against redundant oncogenes are more potent than single drugs 38,39 .…”
Section: Abemaciclibmentioning
confidence: 99%